Determinant factors of transfer of training among UiTM academic staff at Institute of Leadership and Development - Nik Sarina Nik Md Salleh
Previous empirical studies have identified the failure of transfer of training among employees, regardless of job sectors. Thus, this study identified the level of transfer of training as perceived by the academic staff of Universiti Teknologi MARA (UiTM). It was also investigated whether employee demographic factors (gender, age, marital status, length of service and types of training) have significant differences on transfer of training. The relationships between employee readiness (attitude, organisational commitment, abilities and motivation to learn), training design (error management and perceived importance), work environment (supervisor's role and opportunity to use) and transfer of training among the academic staff of UiTM were also examined. In addition, this study also aimed to determine if motivation to transfer mediates the relationships between employee readiness, training design, work environment and transfer of training. A quantitative and questionnaire survey method was employed in this study. A total of 258 academic staff of UiTM as participants of training courses at Institute of Leadership and Delevelopment (lLD), UiTM were selected and notified through e-mail to participate in an online survey. 238 responses were received and found usable for the final analysis using the Structural Equation Model - Partial Least Square (SEM-PLS). The results found that the level of transfer of training was moderate among the academic staff of UiTM. Gender, age, marital status and types of training also had significant differences on transfer of training. The findings also revealed that abilities, error management. supervisor's role and opportunity to use had significant and positive relationships with transfer of training. Moreover, the study confirmed the mediating effects of motivation to transfer on the relationships between error management, opportunity to use and transfer of training. Overall, the study had successfully developed a model of transfer of training for UiTM's academic staff which was influenced by abilities, error management. supervisor's role and opportunity to use.